2012
DOI: 10.1039/c2ee02272a
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant promoted solid amine sorbents for CO2capture

Abstract: A new strategy to improve the CO 2 capture performance of solid amine sorbents has been developed based on the balance of CO 2 kinetic diffusion and thermodynamic sorption. The CO 2 -neutral surfactant was introduced into polyethyleneimine (PEI) to create extra CO 2 transfer pathways, facilitating CO 2 diffusion into the deeper PEI films. Consequently, the sorbents offered increased amount of reactive sites and higher utilization efficiency of amine groups, leading to a dramatically enhanced CO 2 dynamic capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
161
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(176 citation statements)
references
References 44 publications
(63 reference statements)
7
161
3
5
Order By: Relevance
“…To further advance the adsorbents for low-concentration CO 2 capture, we use a facilitating CO 2 diffusion strategy raised in our previous contributions. 61 Three polymer surfactants (Span80, CTAB, and PEG) were added to the PEI at a fixed HP2MGL/PEI/surfactant weight ratio of 45/50/5. The adsorption capacities of the surfactant-promoted adsorbents exposed to 400 and 5000 ppm CO 2 /N 2 gas mixtures at 25 C are shown in Figure 7.…”
Section: Effect Of Diffusion Additives On Co 2 Adsorptionmentioning
confidence: 99%
“…To further advance the adsorbents for low-concentration CO 2 capture, we use a facilitating CO 2 diffusion strategy raised in our previous contributions. 61 Three polymer surfactants (Span80, CTAB, and PEG) were added to the PEI at a fixed HP2MGL/PEI/surfactant weight ratio of 45/50/5. The adsorption capacities of the surfactant-promoted adsorbents exposed to 400 and 5000 ppm CO 2 /N 2 gas mixtures at 25 C are shown in Figure 7.…”
Section: Effect Of Diffusion Additives On Co 2 Adsorptionmentioning
confidence: 99%
“…The regeneration performance of CO 2 adsorbents is an important parameter, as the adsorbents should retain stable CO 2 adsorption performance for long-term cyclic operation [55]. In this study, the CO 2 adsorption capacity slightly decreased when the adsorptionedesorption process of the biochar was continuously repeated, as shown in Fig.…”
Section: Co 2 Adsorption On Biochar Produced By Microwave Pyrolysismentioning
confidence: 96%
“…Wang et al [52] concluded that TEPA was better distributed with the help of the template [alcohol polyoxyethylene ether (A (EO) 9)]. Ling and coauthors [60] utilized nine surfactants as promoters to facilitate the CO 2 diffusion from the surface into the bulk of PEI. As a result, nonionic surfactant sorbitan monooleate (Span80) was found to be an optimal candidate to promote CO 2 diffusion process.…”
Section: Introductionmentioning
confidence: 98%